2001
DOI: 10.1103/physrevlett.86.4596
|View full text |Cite
|
Sign up to set email alerts
|

Modified Critical Correlations Close to Modulated and Rough Surfaces

Abstract: Correlation functions are sensitive to the presence of a boundary. Surface modulations give rise to modified near surface correlations, which can be measured by scattering probes. To determine these correlations, we develop a perturbative calculation in deformations in height from a flat surface. The results, combined with a renormalization group around four dimensions, are also used to predict critical behavior near a self-affinely rough surface. We find that a large enough roughness exponent can modify surfa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 32 publications
0
15
0
Order By: Relevance
“…These results in two dimensions have been interpreted in terms of a scale-dependent distribution of opening angles of the fractal boundary [259]. The same analogy has been evoked in the discussion of the surface critical behaviour of self-affine surfaces in [256,257].…”
Section: Semi-infinite Systems With Surface Imperfectionsmentioning
confidence: 77%
See 2 more Smart Citations
“…These results in two dimensions have been interpreted in terms of a scale-dependent distribution of opening angles of the fractal boundary [259]. The same analogy has been evoked in the discussion of the surface critical behaviour of self-affine surfaces in [256,257].…”
Section: Semi-infinite Systems With Surface Imperfectionsmentioning
confidence: 77%
“…Using a perturbative calculation in the deformations in height from a flat surface they showed that the leading power law decay of the correlations is the same as for a flat surface, but with a modulated amplitude reflecting the shape of the surface [256,257].…”
Section: Semi-infinite Systems With Surface Imperfectionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Not surprisingly, surface randomness modifies the critical behavior near the surface [2], yet the common expectation is for the bulk properties to remain intact. In this Letter we show that arbitrarily weak surface disorder destroys long range order in the bulk of a system of continuous symmetry at the arbitrarily low temperature.…”
mentioning
confidence: 99%
“…In a previous Letter [30], we showed that the shape of the surface has a distinct influence on the properties of an adjacent medium with long-range correlations. Here we demonstrate this in more detail for two-point correlation functions near a critical point of the medium, for both cases (i) and (ii) outlined above.…”
Section: Introductionmentioning
confidence: 99%